Admirals, generals, and American foreign policy, 1898-1914 - Challener, Richard D. (Princeton legacy library., 1973)
After the Spanish-American War the United States, both by design and by accident, became involved in the Caribbean and the Far East on a scale that would have seemed highly improbable before 1898. As an ""emerging"" world power, the United States had to grapple with new issues, among them the role of military men and military power in protecting and advancing America's position in the world. Richard D. Challener has examined civil-military relationships in the period 1898-1914 to answer the following questions: To what extent did army and navy officers develop opinions on foreign policy issu.